2016
DOI: 10.1177/0042085916641173
|View full text |Cite
|
Sign up to set email alerts
|

Two Views of Culture and Their Implications for Mathematics Teaching and Learning

Abstract: In this article, the authors present an analysis of two views of culture reflected in equity scholarship and their implications on research and mathematics teaching. In doing so, they draw on two interrelated theoretical orientations to describe instructional practices that support equitable learning opportunities in mathematics classrooms. These two orientations are grounded in contrasting views of culture. They discuss the contributions of and the tensions associated with each orientation, and argue for a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 68 publications
(72 reference statements)
0
22
0
2
Order By: Relevance
“…(See, also, Westaway 2019 and Westaway and Graven 2019 for further discussion around some South African primary teachers' lowered expectations for certain groups of students.) Reduction of cognitive challenge flouts two important points made by Hodge and Cobb (2019): firstly, that 'mathematically rigorous tasks are critical in supporting instructional practices that are equitable in terms of student learning opportunities'; secondly, that 'issues of access are especially important in the case of students who are members of historically underserved groups and can have a profound influence on their future educational and economic opportunities [emphasis added]' (p. 870).…”
Section: Language Immersion Practices In Two South African Mathematicmentioning
confidence: 99%
“…(See, also, Westaway 2019 and Westaway and Graven 2019 for further discussion around some South African primary teachers' lowered expectations for certain groups of students.) Reduction of cognitive challenge flouts two important points made by Hodge and Cobb (2019): firstly, that 'mathematically rigorous tasks are critical in supporting instructional practices that are equitable in terms of student learning opportunities'; secondly, that 'issues of access are especially important in the case of students who are members of historically underserved groups and can have a profound influence on their future educational and economic opportunities [emphasis added]' (p. 870).…”
Section: Language Immersion Practices In Two South African Mathematicmentioning
confidence: 99%
“…Moreover, research evidence has shown that the ways through which a person develops his or her 2 / 18 http://www.iejme.com mathematical competence in different social practices (for example, in school or in family daily life) are usually characterized by discontinuity and the students' school mathematical practice does not imply their performing in out of school relevant practices, especially for groups not belonging to the dominant social group, such as immigrant groups (Abreu, Gorgorio, & Boistrup, 2018;Takeuchi, 2018). On the other hand, some researchers have mentioned that such discontinuities should not be viewed as obstacles, but as a variety of practices that the students can negotiate in participating in classroom activities (Hodge & Cobb, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…I argue that our obligation as educators, teachers, researchers is to learn about and from these funds of knowledge and build on them for the advancement of students in school. Hodge and Cobb (2016) describe this approach as an example of the "Cultural Alignment Orientation", which they say "has become the default theoretical framework for research on issues of equity in mathematics education" (p. 2). In this orientation, the authors say that the focus is on "aligning the practices established in the mathematics classroom with the out-of-school practices in which students participate.…”
Section: Some Contextmentioning
confidence: 99%